2020
DOI: 10.3389/fnbot.2020.593732
|View full text |Cite
|
Sign up to set email alerts
|

The Human Takes It All: Humanlike Synthesized Voices Are Perceived as Less Eerie and More Likable. Evidence From a Subjective Ratings Study

Abstract: Background: The increasing involvement of social robots in human lives raises the question as to how humans perceive social robots. Little is known about human perception of synthesized voices.Aim: To investigate which synthesized voice parameters predict the speaker's eeriness and voice likability; to determine if individual listener characteristics (e.g., personality, attitude toward robots, age) influence synthesized voice evaluations; and to explore which paralinguistic features subjectively distinguish hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 89 publications
3
33
0
Order By: Relevance
“…Voice distortion: Distorting natural human voices as auditory stimuli [e.g., Baird et al 2018;Kühne et al 2020]. This technique has been used to test whether the UV effect can occur solely within audition.…”
Section: Stimulus Rangementioning
confidence: 99%
“…Voice distortion: Distorting natural human voices as auditory stimuli [e.g., Baird et al 2018;Kühne et al 2020]. This technique has been used to test whether the UV effect can occur solely within audition.…”
Section: Stimulus Rangementioning
confidence: 99%
“…To date, we know only little about whether realistically human-sounding computer voices would elicit particularly positive or negative user responses, and if it matters whether we think of a more social application such as a talking care robot or a more formal one such as a financial assistant. In a recent attempt to shed light on this matter, Kühne et al (2020) found, contrary to their expectations, that participants generally liked highly human-like computer voices more than synthetically sounding ones. Against the background of the popular Uncanny Valley hypothesis (Mori, 1970) and empirical findings on visual or behavioral human-likeness in robots (Bartneck et al, 2007;Mara and Appel, 2015a,b;Appel et al, 2016;Mathur and Reichling, 2016), however, it could be assumed that a too realistic imitation of the human would lead to aversive responses.…”
Section: Introductionmentioning
confidence: 65%
“…When ordering at drive thru window or calling a travel agency, respondents indicated that the use of a human-like voice could set unrealistic expectations about the types of capabilities and interactions available. Other work on perceptions of synthetic voices has noted similar issues (Kühne, Fischer, & Zhou, 2020;Poushneh, 2021). To help address the potential gap between user expectations and the functional capabilities of a highfidelity computer-generated voice, some respondents emphasized the importance of a disclaimer.…”
Section: Discussionmentioning
confidence: 99%